Analysis of Laboratory Testing of VNotch Weirmeter With Two Angle of Notch and Depth Variation That Affect Coefficient Of Discharge - S Syahri, Fauzan
Weirmeter is a measuring device that can be used to measure water flow in open channel. Measurement of the water level that passing through the channel and then converted with an equation to get the value of water discharge as a basic concept that used by this measuring device. Weirmeter can be distinguished by the form, thick, and edge-shape of the notches. The testing of V-notch weirmeter is conducted in this final project. It is done on two angles of notches and varied depths. Then, the values of Cd which is obtained from data processing are plotted into curves and compared with literature. How depth affects the value of Cd is then analyzed. Value of coefficient discharge (Cd) closest to literature is 0,58 at 2,5 cm of crest width and 22,3 cm of depth at V-notch weir 600. Meanwhile, value of Cd at V-notch weir 900 that closest to literature is 0,55 at 1 cm of crest width and 22,3 cm of depth.